Understanding the geographic pattern of diffusion of modern crop varieties in India: A multilevel modeling approach - Kumar, Anjani; Hazrana, Jaweriah; Negi, Digvijay S.; Tripathi, Gaurav; Birthal, Pratap Singh (International Food Policy Research Institute, 2020)
In this paper, we seek to quantify the relative importance of various geographical and administrative factors affecting the diffusion process of modern crop varieties in India. Our study relies on a multilevel modeling approach and uses pan-Indian, household-level data on the adoption of different varieties of rice, wheat and maize. Findings indicate that household-level differences explain larger variation in the adoption of modern crop varieties, but the contextual effects of state actions also play an important role in the diffusion process. These contextual effects are larger for commercial crops than for subsistence crops. Although level-specific recommendations are beyond the scope of this paper, our findings imply a need for strengthening linkages between research and extension systems, and better coordination of programs and strategies across different geographical levels for dissemination of modern crop varieties.